Two-dimensional protein analysis of neural stem cells - Maurer, Martin H. (Expression profiling in neuroscience, 2012)
The current protocol describes in the first part the isolation and culture of neural stem and progenitor cells. In the second part, the two-dimensional gel electrophoresis of neural stem and progenitor cells is explained, consisting of sample preparation, first-dimensional isoelectric focusing, second-dimensional acrylamide gel electrophoresis, protein staining, and image digitalization. The third part concentrates on the software analysis of two-dimensional gel images and the bioinformatical processing.